1997
DOI: 10.1002/(sici)1097-0193(1997)5:3<206::aid-hbm5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex and hand motor skills: Structural compliance in the human brain

Abstract: Recent studies in humans and nonhuman primates have shown that the functional organization of the human sensorimotor cortex changes following sensory stimulation or following the acquisition of motor skills. It is unknown whether functional plasticity in response to the acquisition of new motor skills and the continued performance of complicated bimanual movements for years is associated with structural changes in the organization of the motor cortex. Professional musicians, especially keyboard and string play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
238
3
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 390 publications
(257 citation statements)
references
References 59 publications
11
238
3
5
Order By: Relevance
“…Furthermore, given the relatively small sample size and diversity of age ranges in the cohorts of these studies (listed in Table 2), further investigation and replication may be needed in order to validate some of their conclusions. For instance, the greater symmetry of the central sulcus in professional keyboard players, originally reported by Amunts et al (1997) was independently replicated 13 years later in a group of Chinese musicians by Li et al (2010). Longitudinal studies and larger datasets will be crucial to shedding light on the mechanisms that mediate interhemispheric structural plasticity in the brain.…”
Section: Gender Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, given the relatively small sample size and diversity of age ranges in the cohorts of these studies (listed in Table 2), further investigation and replication may be needed in order to validate some of their conclusions. For instance, the greater symmetry of the central sulcus in professional keyboard players, originally reported by Amunts et al (1997) was independently replicated 13 years later in a group of Chinese musicians by Li et al (2010). Longitudinal studies and larger datasets will be crucial to shedding light on the mechanisms that mediate interhemispheric structural plasticity in the brain.…”
Section: Gender Effectsmentioning
confidence: 97%
“…For instance, an analysis of the planum temporale in professional musicians with and without perfect pitch, and non-musician controls (Schlaug et al, 1995) found that musicians with perfect pitch displayed up to twice as much asymmetry compared with musicians without perfect pitch and controls, primarily due to a smaller volume on the right hemisphere (Keenan et al, 2001). A prior study had found that right-handed male professional keyboard players exhibited greater symmetry in the central sulcus, as compared to age-matched controls (Amunts et al, 1997). In addition, the depth of the sulcus was negatively correlated with the age at which musicians began bimanual training (Amunts et al, 1997).…”
Section: Experiential and Environmental Factors Influencing Plasticitymentioning
confidence: 99%
“…Indeed, neuroimaging studies indicate that professional musicians exhibit larger grey matter volume in the primary motor cortex (Amunts et al, 1997;Gaser & Schlaug, 2003;Elbert et al, 1995) and cerebellum (Hutchinson et al, 2003), relative to non-musicians. Furthermore, structural enlargements in the primary motor cortex (M1) appear to correspond to the type of instrument that an individual specializes in (Elbert et al, 1995;Bangert & Schlaug, 2006).…”
mentioning
confidence: 99%
“…This population began their practice in childhood thereafter practiced intensely for many years. Researchers have suggested that the differences observed between musicians and nonmusicians were related to long-term and intensive practice on a musical instrument (Gaser & Schlaug, 2003;Norton et al, 2005) and early commencement of practice (Amunts et al, 1997;Watanabe, Savion-Lemieux, & Penhune, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found that musicians have performed better than non-musicians on auditory processing (Chartrand & Belin, 2006;Špajdel, Jariabková, & Riečanský, 2007;Strait, Kraus, Parbery-Clark, & Ashley, 2010) and fine motor abilities (Amunts et al, 1997;Hughes & Franz, 2007;Spilka, Steele, & Penhune, 2010).…”
Section: Introductionmentioning
confidence: 97%